Application of functionally graded materials for severe plastic deformation and smart materials: experimental study and finite element analysis - Jamian, Saifulnizan (2012)
Functionally graded materials (FGMs) refer to the composite materials where the compositions or the microstructures are locally varied so that a certain variation of the local material properties is achieved. Determination of compositional gradient and the process of making an FGM are dependent on its intended use. In this study, new possible applications of FGM and its production process were investigated. Three possible application of FGM were proposed. First, the novel technique in producing ultra fine grain of difficult-to-work materials by equal-channel angular pressing (ECAP) process at ambient temperature was developed by using FGM. For this study, Ti as the difficult-to-work material was tightly encapsulated in a hollow host material made of Al-based FGM matrix. The Al-based FGM as a host material assists the deformation of Ti. The ECAP process was simulated by the finite element method (FEM) to determine the appropriate compositional gradient of Al-based FGM and the position to embed Ti wire. FEM was conducted with Ti embedded into a different host material type as well as different die channel geometry. The strain distribution of the specimen after a single ECAP pass was analyzed. From the obtained results, it is found that the strain distribution in Ti is strongly influenced by the host material and the shape of the die channel. An experimental work was carried out to confirm the ability of the proposed technique in producing ultra fine grain of Ti. The host material was prepared by embedding Al-Al3Ti alloy into Al. Three types of the Al-Al3Ti alloys with different Al3Ti volume fractions were used to prepare the host materials. ECAP for specimens was carried out for up to eight passes by route A. The microstructure and hardness of ECAPed specimens were investigated. The changes in microstructure and the increase in the hardness value of Ti with increased number of ECAP passes are evidences showing that Ti is successfully deformed by this technique. Second, new types of FGM crash boxes with stepwise strength gradient in longitudinal directions were proposed. The property of the proposed FGM crash boxes were analyzed using FEM. Crash behavior of the crash box under axial quasi-static and dynamic impact loads were studied. The obtained load-displacement curves and the crash failure patterns then were evaluated to assess the effect of the stepwise strength gradient of the crash-box. II Moreover, four different shapes of cross-sectional i.e. square, circle, pentagon and hexagon were considered. The results show that the FGM crash box is superior to than the homogeneous crash box in overall crashworthiness. Although there were no trigger mechanism introduced, the FGM crash boxes experience the progressive crushing initiated at the impact side. Third, the FGMs were applied in pipe and pressure vessel field. A solution procedure for finite element thermo-visco-plasticity and creep analysis in an FGM thick-walled pressure vessel subjected to thermal and internal pressure was presented. The thickwalled pressure vessel was replaced by a system of discrete rectangular cross-section ring elements interconnected along circumferential nodal circles. The property of FGM was assumed to be continuous function of volume fraction of material composition. The thermo-visco-plasticity and creep behavior of the structures were obtained by the use of an incremental approach. The obtained results show that the material composition significantly affects the stress as a function of time at the inside and outside surface of thick-walled pressure vessel. The use of FGM can adjust the stress distribution in the structure. Moreover, one of the FGM fabrication method, centrifugal casting, was investigated. Two types of centrifugal casting method namely, centrifugal solid-particle method (CSPM) and centrifugal mixed-powder method (CMPM), were used to fabricate Al/SiC FGM. Formations of graded distribution of SiC particles within molten Al by CSPM and CMPM under huge centrifugal force were examined and simulated. The movement of SiC particles in viscous liquid under centrifugal force was explained theoretically based on Stoke’s law. The effect of composition gradient of particles on viscosity was taken into account. Also, the effect of temperature distribution on viscosity and density were considered. A computer code to simulate the formation of compositional gradient in an Al/SiC FGM manufactured by CSPM and CMPM was developed. From the obtained results, it was found that the SiC particles can be graded from inner to outer surface of Al/SiC FGM by CSPM. Meanwhile by CMPM, the SiC particles can be dispersed on the surface of Al/SiC FGM. The graded distribution in Al/SiC FGM under huge centrifugal force was significantly affected by the mold temperature but less affected by the initial temperature of molten Al and casting atmosphere.